Political Corporate Social Responsibility in Indonesia: Is A Collaboration - Sumitro Sarkum (IKA BINA EN PABOLO : PENGABDIAN KEPADA MASYARAKAT, 2023)
Practice-Political CSR companies in Indonesia cultivate a niche that leads to a corporate charity so that CSR becomes a political phenomenon in collaboration with the government. CSR politics that should be integrated in the hierarchy of companies as their management strategies and policies remains to be underestimated by most businesses in Indonesia. The essence and significance of CSR is still not fully readable by business people, so CSR itself is just an implementation of the demands of society. The purpose of this study is to examine the politics of Corporate Social Responsibility in Indonesia. Conventionally, corporate social responsibility is closely related to the achievement of sustainable economic activities. Sustainability of economic activities is not only related to social responsibility but also related to corporate accountability to society and the nation. The implementation of social responsibility is not based on a force by the society, government or other parties, but it is sourced from the intention, commitment and business behavior that drives the implementation. This research method uses qualitative approach that is literature search about CSR politics in Indonesia. The method of tracking corporate social responsibility is a qualitative approach which is observed through publications on the issue of corporate social responsibility and its life cycle. The data collected is expressed in the form of statements aimed at understanding social phenomena from a perspective. This research method is also used to understand rational reality as subjective reality especially CSR politics in Indonesia. The results show that the obligation to implement CSR is interpreted by imaging to gain legal and social legitimacy that makes the economic dependence on ignorance of the true meaning and paradigm of CSR. Corporate social responsibility is just a program of assistance to avoid a force from other parties as a tool to form a good image, without any ongoing empowerment towards a better direction in accordance with the business ethics paradigm.